Getting to know you: The development of intercultural competence as an essential element in learning Mandarin (UCL Press, 2014)
The role of cultural dimensions in the teaching of Chinese as a foreign language in the UK is not as fully understood as it needs to be, especially in relation to developing students' abilities with intercultural communication. This paper adopts an ecological perspective on learning another language and seeks to contribute to the field of teaching and learning a foreign language through an investigation of the perceptions and experiences of university-based learners of Chinese. Learners' perceptions and experiences might productively be conceptualized with an ecology metaphor which provides analysts with a complex view of the learning and use of language based on a consideration of time and space. This present study focuses on one aspect of a broader research project in which the author investigated a group of students studying Chinese at universities in London and other British cities whose construction of culture and intercultural competence while learning Chinese as a foreign language was based on their learning experiences and intercultural encounters. In what follows we consider the concept of 'language distance' in order to understand both the linguistic and social space that students of Chinese need to overcome. Drawing from the research data, the paper also considers the notion of intercultural communication and learning as arising from a seamless interaction between different layers of fluid social processes. The paper argues that Chinese as a foreign language in higher education can provide resources for developing intercultural dimensions of learning. The paper concludes by stressing that changes in approach to teaching and learning Chinese are increasingly necessary because of the rapid changes that are taking place within the social and political ecology of China and the Chinese language.